PENGARUH PENDIDIKAN DAN PELATIHAN DAN DISIPLIN TERHADAP KINERJA ASN PADA DINAS PENDIDIKAN DAN KEBUDAYAAN KABUPATEN SITUBONDO - Anitasari, Eka Yuli; Fandiyanto, Randika; Syahputra, Hendra (Fakultas Ekonomi dan Bisnis, 2023)
The research was conducted with the aim of knowing the relationship between the level of education and training variables (X1) based on the performance (Y2) of ASN employees. The results of the M Test show that the relationship between variables X1 (Education and Training) and X2 (Discipline) is not related to each other in influencing Y1 (Job Satisfaction) or Y2 (Performance). The P value of the influence of Education and Training (X1) on job satisfaction (Y1) is 0.000, meaning this value is below 5% and the Original Sample value is Positive. Which means that Education and Training (X1) positively and significantly influence job satisfaction (Y1) (H1 Accepted). Therefore, education and training (X1) is a form of appreciation that is needed and needed by ASN employees.